2023
DOI: 10.3348/kjr.2023.0015
|View full text |Cite
|
Sign up to set email alerts
|

Radiology Residents’ Independent Diagnosis of Appendicitis Using 2-mSv Computed Tomography: A Secondary Analysis of a Large Pragmatic Randomized Trial

Abstract: Objective To compare the diagnostic performance and clinical outcomes of 2-mSv computed tomography (CT) and conventional-dose CT (CDCT), following radiology residents’ interpretation of CT examinations for suspected appendicitis. Materials and Methods Altogether, 3074 patients with suspected appendicitis aged 15–44 years (28 ± 9 years, 1672 females) from 20 hospitals were randomly assigned to the 2-mSv CT (n = 1535) or CDCT (n = 1539) groups in a pragmatic trial from De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The present study showed a similarly low rate of normal CT scans in the CT and observation groups (37.5% vs. 34.5%, accordingly). If the diagnosis remains unclear after repeated ultrasound examinations (by two independent radiologists) and a CT scan is indicated, some authors suggest that low-dose CT may be an option since diagnostic accuracy and clinical results for suspected appendicitis did not differ between the 2-mSv CT and conventional-dose CT (CDCT) groups [ 25 ]. The OPTICAP study showed that the ability not only to diagnose acute appendicitis but also to differentiate between complicated and uncomplicated cases for individuals with a high risk of acute appendicitis was equally accurate with contrast-enhanced low-dose CT and normal CT [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed a similarly low rate of normal CT scans in the CT and observation groups (37.5% vs. 34.5%, accordingly). If the diagnosis remains unclear after repeated ultrasound examinations (by two independent radiologists) and a CT scan is indicated, some authors suggest that low-dose CT may be an option since diagnostic accuracy and clinical results for suspected appendicitis did not differ between the 2-mSv CT and conventional-dose CT (CDCT) groups [ 25 ]. The OPTICAP study showed that the ability not only to diagnose acute appendicitis but also to differentiate between complicated and uncomplicated cases for individuals with a high risk of acute appendicitis was equally accurate with contrast-enhanced low-dose CT and normal CT [ 26 ].…”
Section: Discussionmentioning
confidence: 99%